Cenh3: An Emerging Player in Haploid Induction Technology - Britt, Anne B.; Kuppu, Sundaram (Frontiers in Plant Science, 2016)
True-breeding lines are required for the development and production of crop varieties. In a classical breeding approach these lines are obtained through inbreeding, and often 7-9 generations of inbreeding is performed to achieve the desired level of homozygosity, over a period of several years. In contrast, the chromosomes of haploids can be doubled to produce true-breeding lines in a single generation. Over the last century, scientists have developed a variety of techniques to induce haploids and doubled haploids, though these techniques apply only to particular crop varieties. Ravi and Chan, (2010) discovered that haploids could be obtained in Arabidopsis through the manipulation of the centromere-specific histone 3 variant, CenH3. Their approach, which involved extensive modifications to a transgenic CenH3, held promise of being translated to crop species, and has been successfully employed in maize (see REF, this issue). Refinements of this technology have since been developed which indicate that nontransgenic modifications to CENH3 will also induce haploids. The complementation of a cenh3 null by CENH3 from closely related plant species can result in plants that are fertile but haploid-inducing on crossing by CENH3 wt plants- suggesting that introgression of alien CENH3 may produce nontransgenic haploid inducers. Similarly, a remarkably wide variety of point mutations in CENH3, inducible by chemical agents, have recently been shown to result in haploid induction on crossing by wild-type CENH3 plants. These CENH3-variant plants grow normally, are fully fertile on self-pollination, and may be present in existing mutagenized collections.